2012
DOI: 10.1093/jpepsy/jss071
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic and Quantitative Review of Interventions to Facilitate School Reentry for Children With Chronic Health Conditions

Abstract: This analysis provides support for the effectiveness of school reentry interventions and highlights the critical need for more empirical work in this area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(71 citation statements)
references
References 20 publications
0
69
2
Order By: Relevance
“…While the literature was limited by low‐quality studies, it showed consistent support for school re‐entry services. Good school re‐entry services can help maintain academic performance, school engagement and peer relationships, which can improve graduation outcomes and mental health . School re‐entry services can also improve teachers’ cancer knowledge and facilitate a supportive attitude towards the child .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the literature was limited by low‐quality studies, it showed consistent support for school re‐entry services. Good school re‐entry services can help maintain academic performance, school engagement and peer relationships, which can improve graduation outcomes and mental health . School re‐entry services can also improve teachers’ cancer knowledge and facilitate a supportive attitude towards the child .…”
Section: Methodsmentioning
confidence: 99%
“…Most Australian teachers do not complete pre‐service or in‐service training aimed at meeting the needs of children diagnosed with cancer or other chronic illnesses . Teachers may not feel prepared to accommodate the needs of children diagnosed with cancer and have identified specific informational needs that they require before they can deliver support . Considering that 10–20% of all children and adolescents suffer a chronic illness, university curriculums should include training about educational implications and management of chronic illness in schools .…”
Section: Methodsmentioning
confidence: 99%
“…This gives further evidence of the value of this SRP. In comparison to the review by Canter and Roberts [11] in which they identified increased illness/condition-specific knowledge of both teachers and healthy peers, this audit similarly identified an increased awareness of the injury and its associated difficulties to all involved, as well as the themes of feeling supported and reducing fear.…”
Section: Overview Of Findingsmentioning
confidence: 69%
“…Canter and Roberts [11] conducted a quantitative review of research on the effects of school re-entry interventions for children with chronic health conditions. These interventions can take the form of a workshop aiming to increase disease or injury-specific knowledge, and decrease anxiety surrounding the return of an ill child back to the class room, and can also involve discussing the needs and fears of the ill child and of the class.…”
Section: Introductionmentioning
confidence: 99%
“…To encourage the implementation of these interventions, more communication is needed between the medical team and school system. This may be done through the implementation of reentry school programs that have been previously reported to be successful (24). While schools were concerned how PA would impact academic performance, several studies have revealed that exercise does not impair academic performance (25) but rather promotes performance, concentration, memory, and classroom behavior (26).…”
Section: Resultsmentioning
confidence: 99%